Tritoroidal particle rings formation in open microfluidics induced by standing surface acoustic waves. Issue 10 (28th February 2020) - Zheng, Tengfei; Wang, Chaohui; Xu, Chaoping
Abstract: In this paper, the particle movements in a sessile droplet induced by standing surface acoustic waves (SSAWs) are studied. Tritoroidal particle rings are formed under the interaction of acoustic field and electric field. The experimental results demonstrate that the electric field plays an important role in patterning nanoparticles. The electric field can define the droplet shape due to electrowetting. When the droplet approximates a hemisphere, the acoustic radiation force induced by SSAWs drives the particles to form tritoroidal particle rings. When the droplet approximates a convex plate, the drag force induced by acoustic steaming drives the particle to move. The results will be useful for better understanding the nanoparticle movements in a sessile droplet, which is important to explain the mechanism that SSAWs enhance reaction and crystallization in droplet.